Anti-tumor effects of anti-PD-1 antibody, pembrolizumab, in humanized NSG PDX mice xenografted with dedifferentiated liposarcoma. (28th May 2020) - Choi, Bongkum; Lee, Joo Sang; Kim, Sung Joo; Hong, Doopyo; Park, Jae Berm; Lee, Ki-Young
Abstract: The efficacy of an immune checkpoint blockade has been demonstrated against various types of cancer, but its suitability has not been fully proven for therapies specifically targeting sarcoma. We conducted a pan-cancer tumor data analysis to identify key immune-related variables strongly associated with sarcoma prognosis, and we explored whether these expected factors are functionally correlated with anti-PD-1 therapy in humanized (Hu) NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice xenografted with dedifferentiated liposarcoma (DDLPS). We found that an abundance of hCD8 + T cells and hNK cells was functionally associated with anti-PD-1 effects in the Hu-NSG DDLPS mice. Phenotypically, these cells were shown to be hCD8 + IFNγ +, hCD8 + PD-1 +, hCD8 + Ki-67 +, hCD56 + IFNγ +, hCD56 + PD-1 +, and hCD56 + Ki-67 + cells and were enriched in splenocytes and tumor-infiltrating lymphocytes (TILs) of Hu-NSG DDLPS mice treated with anti-PD-1 antibody. Moreover, a considerable increase in activated hCD56 + NKp46 + NKG2D +  NK cells was also detected. Our findings suggest that hCD8 + T and hNK subsets play a pivotal role in anti-DDLPS tumor effects of anti-PD-1 therapy. The results provide clinical reference for advanced anti-PD-1 therapy targeting sarcoma tumors including DDLPS. Highlights: The efficacy of immune checkpoint blockade has been never proven in sarcoma. Immune-related variables are associated with the prognosis of sarcoma cancers. hCD8 + T and hNK cells are associated with the anti-PD-1 effects in DDLPS. hCD8 + T and hNK subsets might play a role for anti-DDLPS tumor effects.